Chaotic CS Encryption: An Efficient Image Encryption Algorithm Based on Chebyshev Chaotic System and Compressive Sensing - Sun, Mingliang; Yuan, Jie; Li, Xiaoyong; Liu, Dongxiao (Computers, materials & continua, 2024)
Images are the most important carrier of human information. Moreover, how to safely transmit digital images through public channels has become an urgent problem. In this paper, we propose a novel image encryption algorithm, called chaotic compressive sensing (CS) encryption (CCSE), which can not only improve the efficiency of image transmission but also introduce the high security of the chaotic system. Specifically, the proposed CCSE can fully leverage the advantages of the Chebyshev chaotic system and CS, enabling it to withstand various attacks, such as differential attacks, and exhibit robustness. First, we use a sparse trans-form to sparse the plaintext image and then use the Arnold transform to perturb the image pixels. After that, we elaborate a Chebyshev Toeplitz chaotic sensing matrix for CCSE. By using this Toeplitz matrix, the perturbed image is compressed and sampled to reduce the transmission bandwidth and the amount of data. Finally, a bilateral diffusion operator and a chaotic encryption operator are used to perturb and expand the image pixels to change the pixel position and value of the compressed image, and ultimately obtain an encrypted image. Experimental results show that our method can be resistant to various attacks, such as the statistical attack and noise attack, and can outperform its current competitors.